Breeding of the innovative varieties of spring barley in the Central Black earth Region - L. M. Eroshenko; A. N. Eroshenko; M. M. Romakhin; N. A. Eroshenko (Зерновое хозяйство России, 2018)
Breeding of the innovative varieties of spring barley in the Central Black earth Region The long-term study of the variety-testing showed that the breeding work with spring barley in the Central Black earth region is of significant success. For the last decades there have been grown several regional and promising varieties of spring barley possessing high and stable productivity and having advantages over the German variety ‘Xanadou’ during the years with different humidity. The breeding and economic value of the best varieties ‘Moskovsky 86’, ‘Yaromir’ and ‘Nadezhny’, selected as the most productive ones in the competitive variety-testing, has been confirmed by the biochemical analysis of grain, that indicate not only yield increase, but also improvement and stability of the indexes of grain quality of new developed barley varieties. It is the result of the development and application of new methods of estimation and selection of the breeding material, development of promising initial material. The use of the indexes of stability allowed revealing the varieties with tolerance to stress factors and high productivity in dry years as well as in wet years of growing. The ecologic-genetic approach in the breeding process gave an opportunity to obtain true ecological characteristics of the spring barley varieties selected in Moscow RIA to find highly adaptive varieties. The correlation analysis of interconnection of grain productivity and elements of yield structure showed the importance of the productive stand in the increase of plasticity of barley varieties. The data about the level of the development of economic-valuable traits depending on the conditions of the vegetation period of different varieties in different years of use, allowed establishing the role of selection in productivity increase and substantiating the further direction of its improvement. The purposeful work in the improvement of variety resistance to infectious diseases and lodging has been a prerequisite of the success in the improvement of the adaptive potential of the varieties. Thus, the application of the modern selection methods allowed developing the innovative varieties with a vast agro ecological adaptive ability and resistance to diseases, able to produce stable yields with high technological qualities of grain.